Effects of Fructus Chaenomelis on longitudinal bone growth in adolescent rats - Chung hun Lee,; Do Yeon Lee,; Ji Hoon Jeong,; Tae Jin Lee,; Eon Sub Park, (International Journal of Phytomedicine, 2014)
Effects of Fructus Chaenomelis on longitudinal bone growth in adolescent rats